Painful bladder: Case studies - Bailly, Greg (Canadian Urological Association Journal, 2013)
As part of the program at the 3rd Annual Canadian Urology Forum (2013), participants engaged in interactive discussions of difficult cases throughout the event. The following is a summary of discussions pertaining to two cases illustrating the difficulties in diagnosis and management of bladder pain symptoms.